Current Threats to Sustainable Shipping – from War Risks to Climate Changes - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V. (Odesa : Publishing House Helvetica, 2024)
The article analyzes the current global risks faced by the maritime industry and explores potential solutions to minimize their negative impact on supply chains. It highlights the damaging effects of regional armed conflicts and the challenges associated with different stakeholders working together to ensure connectivity in combat zones at sea. The article also examines the impact of climate change on maritime transport, using the Suez and Panama Canals as examples. In both instances, the instability factors cause significant changes to shipping routes, volumes, and types of cargo transported by sea. These effects can also be observed beyond the region affected by the destabilizing factors or the corresponding types of cargo.
Kivalov S. Current Threats to Sustainable Shipping – from War Risks to Climate Changes / S. Kivalov // Lex Portus. - Odesa : Publishing House Helvetica, 2024. - 10(2). - Р. 15–24. URI: https://doi.org/10.62821/lp10202
Keywords: navigation; maritime industry; war risks; climate change; Red Sea; Black Sea; security